2017
DOI: 10.4253/wjge.v9.i9.494
|View full text |Cite
|
Sign up to set email alerts
|

Successful endoscopic removal of three embedded esophageal self-expanding metal stents

Abstract: In the report, we describe a case of refractory benign esophageal strictures from esophageal cancer after an operation for the placement of three partially covered self-expanding metal stents (SEMSs), which were all embedded in the esophageal wall. Using the stent-in-stent technique, the three embedded SEMSs were successfully removed without significant complications. To the best of our knowledge, few cases of the successful removal of multiple embedded esophageal SEMSs have been reported in the literature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Different methods for endoscopic removal of an embedded PCSEMS have been described [100][101][102][103][104][105][106]. Most studies have reported on the use of the stent-in-stent technique, which relies on the placement of an additional FCSEMS fully overlapping the location of the embedded PCSEMS.…”
Section: Factors Predicting Successful Treatmentmentioning
confidence: 99%
“…Different methods for endoscopic removal of an embedded PCSEMS have been described [100][101][102][103][104][105][106]. Most studies have reported on the use of the stent-in-stent technique, which relies on the placement of an additional FCSEMS fully overlapping the location of the embedded PCSEMS.…”
Section: Factors Predicting Successful Treatmentmentioning
confidence: 99%
“…For patients with embedded esophageal stent and hyperplasia-induced stenosis, the SIS technique under endoscopy has been demonstrated to be effective and safe (7,17,19). We therefore adapted the SIS technique for the interventional radiology approach.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with embedded esophageal stent and hyperplasia-induced stenosis, the SIS technique under endoscopy has been demonstrated to be effective and safe 7,16,18 . We therefore adapted the SIS method for the interventional radiology approach.…”
Section: Discussionmentioning
confidence: 99%